Activation of Toll-like receptor 2 reveals microbial contamination beyond endotoxins on micro- and nanoplastics - Øyvind P. Haugen; Itziar Polanco-Garriz; Victor Alcolea-Rodriguez; Raquel Portela; Rita Bæra; Hamed Sadeghiankaffash; Jana Hildebrandt; Dmitri Ciornii; Korinna Altmann; Francesco Barbero; Ivana Fenoglio; Julián J. Reinosa; et al. (Toxicology in Vitro, 2026)

Comparison of Curie-point pyrolysis with tetramethylammonium hydroxide (TMAH) and base catalyzed methanolysis in leaf and root biomarker decomposition studies - J.G. Altmann; B. Jansen; M. Palviainen; K. Kalbitz (Organic Geochemistry, 2026)

P22-46 Effects of plastic nanoparticles, paracetamol, ibuprofen and their mixtures on steroidogenesis in vitro - L. Bozicevic; N. Peranić; J. Hildebrandt; K. Altmann; I. Vinković Vrček (Toxicology Letters, 2025)

P22-44 Estrogenic activity of nanoplastics in vitro - N. Peranić; L. Božičević; K. Altmann; J. Hildebrandt; R. Portela; M. Banares; I. Vinković Vrček (Toxicology Letters, 2025)

P25-29 Interactions of plastic nanoparticles with fluoxetine and carbamazepine in estrogen receptor activation in vitro - L. Božičević; V. Vrček; N. Peranić; N. Kalčec; J. Hildebrandt; K. Altmann; I. Vinković Vrček (Toxicology Letters, 2024)

P21-65 Androgenic and anti-androgenic effects of nanoplastics - N. Peranić; L. Božičević; K. Altmann; J. Hildebrandt; R. Portela; M. Banares; I. Vinković Vrček (Toxicology Letters, 2024)

P15-02 Assessing immune-related effects of nanoplastics on primary human monocytes in vitro - N. Negi; H. Hjertholm; M. Lislien; N.M. Smith; D. Behmen; K. Altmann; J. Hildebrandt; M. Andreassen; B.B. Granum; R. Pieters; H. Dirven; I. Snapkow (Toxicology Letters, 2024)

S04-01 Inflammation-related key events stimulated by micro- and nanoplastics - A. van den Berg; K. Adriaans; E. Hoppener; L. Parker; A. Boersma; K. Altmann; J. Legler; R. Pieters (Toxicology Letters, 2024)

Does climate variability influence the demography of wild primates? Evidence from long‐term life‐history data in seven species - Fernando A. Campos; William F. Morris; Susan C. Alberts; Jeanne Altmann; Diane K. Brockman; Marina Cords; Anne Pusey; Tara S. Stoinski; Karen B. Strier; Linda M. Fedigan (Global Change Biology, 2017)
Earth's rapidly changing climate creates a growing need to understand how demographic processes in natural populations are affected by climate variability, particularly among organisms threatened by extinction. Long‐term, large‐scale, and cross‐taxon studies of vital rate variation in relation to climate variability can be particularly valuable because they can reveal environmental drivers that affect multiple species over extensive regions. Few such data exist for animals with slow life histories, particularly in the tropics, where climate variation over large‐scale space is asynchronous. As our closest relatives, nonhuman primates are especially valuable as a resource to understand the roles of climate variability and climate change in human evolutionary history. Here, we provide the first comprehensive investigation of vital rate variation in relation to climate variability among wild primates. We ask whether primates are sensitive to global changes that are universal (e.g., higher temperature, large‐scale climate oscillations) or whether they are more sensitive to global change effects that are local (e.g., more rain in some places), which would complicate predictions of how primates in general will respond to climate change. To address these questions, we use a database of long‐term life‐history data for natural populations of seven primate species that have been studied for 29–52 years to investigate associations between vital rate variation, local climate variability, and global climate oscillations. Associations between vital rates and climate variability varied among species and depended on the time windows considered, highlighting the importance of temporal scale in detection of such effects. We found strong climate signals in the fertility rates of three species. However, survival, which has a greater impact on population growth, was little affected by climate variability. Thus, we found evidence for demographic buffering of life histories, but also evidence of mechanisms by which climate change could affect the fates of wild primates.

Improved Automatic Segmentation of White Matter Hyperintensities in MRI Based on Multilevel Lesion Features - M. Rincón; E. Díaz-López; P. Selnes; K. Vegge; M. Altmann; T. Fladby; A. Bjørnerud (Neuroinformatics, 2017)